Comprehensive Methodology for Assessing Cumulative Stress and Ways of Overcoming in Post-War Armenia - Hovhannisyan, Sahak (Bulletin of Yerevan University E: Philosophy, Psychology, 2026)
Modern psychological thought has long since moved beyond the simplistic perception of stress as a mere “one-time blow.” Today, we are dealing with a reality where stress is not an event, but a layered memory and a factor that depletes a person’s vital forces, as well as burdens or consumes the body’s resources. For Armenia, this problem has the most vulnerable and strictly targeted recipients: our compatriots forcibly displaced from Artsakh. This is a society for which stress began with the decades-long uncertainty of “no war, no peace,” passed through the horrors of a 44-day war, the nightmare of a pandemic, the humiliation of a prolonged blockade, and ended (or perhaps entered a new phase) with complete displacement. This study is a unique attempt to understand this “distress square,” which in scientific literature is commonly called “cumulative stress.” This phenomenon is defined as the result of multifactorial negative influences, where each new stressor not only adds to the previous one, but also qualitatively changes the structure of psychological resilience. In the study, cumulative stress is considered not only in the light of local experience, but also in the light of global methodological parallels. Thus, the purpose of this article is to present the theoretical and methodological foundations of the research carried out within the framework of the grant program dedicated to the issue of cumulative stress, as well as the intermediate results and practical outcomes of the experimental stage.